The Transformative Role of Artificial Intelligence in Biomedical Research - Baseer, Najma (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Artificial Intelligence (AI) has become a powerful ally in the rapidly changing field of biomedical research, thereby transforming the way scientists tackle intricate medical problems. AI’s incorporation into biological research has opened up new avenues for discovery, diagnosis, and therapy that were previously unimaginable. This editorial examines the diverse applications of AI in biomedical research and emphasizes how it has revolutionized the field in a number of ways.